Intervención pedagógica para la inclusión escolar de estudiantes con necesidades educativas especiales - Pilozo Zambrano, Carolina Isabel (2022)
The pedagogical intervention in the process of school inclusion for students with Learning Difficulty, in the research the objective was to analyze the contribution of the pedagogical intervention in the school inclusion of students with Special Educational Needs. Whose methodology was of mixed approach (Qualitative and Quantitative), allowed to describe and measure the results of the instruments, the types of Research were bibliographical, in charge of selecting, collecting and organizing information through the review of documents to support the research in the same way, descriptive, by means of which the characteristics of the studied sample were determined………..